Recent Advances in Biosensors Using Enzyme-Stabilized Gold Nanoclusters - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Byung-Keun Oh (Biosensors)
Recently, gold nanoclusters (AuNCs) have been widely used in biological applications due to their ultrasmall size, ranging within a few nanometers; large specific surface area; easy functionalization; unique fluorescence properties; and excellent conductivity. However, because they are unstable in solution, AuNCs require stabilization by using ligands such as dendrimers, peptides, DNA, and proteins. As a result, the properties of AuNCs and their formation are determined by the ligand, so the selection of the ligand is important. Of the many ligands implemented, enzyme-stabilized gold nanoclusters (enzyme–AuNCs) have attracted increasing attention for biosensor applications because of the excellent optical/electrochemical properties of AuNCs and the highly target-specific reactions of enzymes. In this review, we explore how enzyme–AuNCs are prepared, their properties, and the various types of enzyme–AuNC-based biosensors that use optical and electrochemical detection techniques. Finally, we discuss the current challenges and prospects of enzyme–AuNCs in biosensing applications. We expect this review to provide interdisciplinary knowledge about the application of enzyme–AuNC-based materials within the biomedical and environmental fields.